A Preliminary Overview of Music Therapy Reimbursement Practice in the United States. - Moore, Kimberly Sena; Peebles, Laurie (Music Therapy Perspectives)
Music therapy services are currently being reimbursed through state and private insurance funding streams, yet to date, there is no known systematic exploration on music therapy reimbursement practices. Such information would be helpful to include when communicating with third-party payers and can assist in tracking reimbursement trends. Thus, we sought to provide baseline information on how music therapy services are currently being reimbursed in the United States, with a focus on approved treatment parameters, referral sources, Current Procedural Terminology (CPT) codes used, and types of music interventions and music therapy experiences implemented. Board-certified music therapists in private practice who had successfully obtained reimbursement for music therapy services between 2012 and 2018 completed a 28-item online survey. In total, 7 respondents provided information on 55 unique reimbursement cases from 5 different states, most of which were based on Medicaid waiver programs. We conducted descriptive analyses to summarize music therapy reimbursement practices. Most of the clients were referred by doctors or physician's assistants. The most common CPT code utilized was 97530 (Therapeutic Activities, one-on-one, each 15 minutes), and most of the International Classification of Diseases, 10th Revision (ICD-10) diagnostic codes were based on specific diagnoses rather than general clinical needs. In most of the cases, reimbursement of music therapy was ongoing, and services incorporated a variety of music therapy methods, with few specific music interventions identified. Most notably, reimbursement practice varied by state; thus, we recommend the creation and dissemination of state-specific surveys.